Nitrogen Starvation Differentially Influences Transcriptional and Uptake Rate Profiles in Roots of Two Maize Inbred Lines with Different NUE - Mascia, Maria (Int J Mol Sci, 2019)
Nitrogen use efficiency (NUE) of crops is estimated to be less than 50%, with a strong impact on environment and economy. Genotype-dependent ability to cope with N shortage has been only partially explored in maize and, in this context, the comparison of molecular responses of lines with different NUE is of particular interest in order to dissect the key elements underlying NUE. Changes in root transcriptome and NH(4)(+)/NO(3)(−) uptake rates during growth (after 1 and 4 days) without N were studied in high (Lo5) and low (T250) NUE maize inbred lines. Results suggests that only a small set of transcripts were commonly modulated in both lines in response to N starvation. However, in both lines, transcripts linked to anthocyanin biosynthesis and lateral root formation were positively affected. On the contrary, those involved in root elongation were downregulated. The main differences between the two lines reside in the ability to modulate the transcripts involved in the transport, distribution and assimilation of mineral nutrients. With regard to N mineral forms, only the Lo5 line responded to N starvation by increasing the NH(4)(+) fluxes as supported by the upregulation of a transcript putatively involved in its transport.